The Use of Illustrated Books to Increase Elementary Students' English Vocabulary - Mas, Muhammad Idris (Pusat Kajian dan Pengembangan Publikasi Ilmiah Institut Agama Islam Hamzanwadi Nahdlatul Wathan Lombok Timur, 2024)
This study addresses the persistent challenge of limited English vocabulary among elementary students, which often hinders their ability to understand and communicate effectively. Many young learners struggle to retain new words when taught through traditional methods lacking engaging visual stimuli. The objective of this research was to investigate the effectiveness of illustrated books in improving vocabulary mastery among elementary school students. A total of 20 students participated in the study. The research applied a pre-test–post-test design. Before the intervention, students took a pre-test that measured their vocabulary knowledge, scoring an average of 20%. They were exposed to illustrated books designed to present target vocabulary through images. At the end of the program, a post-test was administered to assess improvement. The findings revealed a significant increase in students’ vocabulary scores, from 20% in the pre-test to 75% in the post-test. This result indicates that illustrated books provided strong visual support and contextual clues, enabling better comprehension and retention of new words. In conclusion, illustrated books can be an effective tool to enhance vocabulary acquisition among elementary students, making English learning more engaging, memorable, and accessible